2014
DOI: 10.3855/jidc.3553
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of bacterial meningitis in Kosovo

Abstract: Introduction: The purpose of this study was to present the epidemiologic features of bacterial meningitis in the developing country of Kosovo. Methodology: Data were collected from active surveillance of bacterial meningitis cases treated at the University Clinical Center of Kosovo in the years 2000 (first post-war year) and 2010. Results: Meningitis cases in 2000 compared with 2010 showed a 35.5% decline in incidence (from 4.8 to 3.1 cases per 100,000 population) and a decrease in the case fatality rate from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…They detected a lower mortality rate (5% versus 2%) and a lower incidence of neurological complications in children (13% versus 16%) as compared to adults (32% versus 10% and 16% versus 35%, respectively). Neisseria meningitidis was the most common pathogen of bacterial meningitis during both study periods and bacterial meningitis was most common in the pediatric population (15). In this study, during the year 2000, the mean age of pediatric cases was 3.2 years, while for adults it was 41 years.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…They detected a lower mortality rate (5% versus 2%) and a lower incidence of neurological complications in children (13% versus 16%) as compared to adults (32% versus 10% and 16% versus 35%, respectively). Neisseria meningitidis was the most common pathogen of bacterial meningitis during both study periods and bacterial meningitis was most common in the pediatric population (15). In this study, during the year 2000, the mean age of pediatric cases was 3.2 years, while for adults it was 41 years.…”
Section: Discussionmentioning
confidence: 87%
“…Fatality rate in our study was 7.5% and these patients had referred to the hospital late (14). Namani's study compared meningitis cases in 2000 with 2010 and showed a 35.5% decline in incidence and a decrease fatality rate from 10% to 5% (15). They detected a lower mortality rate (5% versus 2%) and a lower incidence of neurological complications in children (13% versus 16%) as compared to adults (32% versus 10% and 16% versus 35%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute bacterial meningitis is the most severe type of meningitis. The incidence rate has decreased and the predominant pathogens have changed in many countries with the introduction of Nm vaccines, Hib vaccine and heptavalent pneumococcal conjugated vaccine (PCV 7) [ 22 28 ]. In the United States, the rate of bacterial meningitis among children < 5 years declined by 55% in the early 1990s when Hib vaccine for infants was introduced [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meningitis is defined as an inflammation of the protective membranes (meninges) that surround the brain and spinal cord (1) , the severity of the meningitis related with microbial causes that may be bacteria, viruses, mycobacteria, parasites and fungi (2) . The incidence of meningitis is usually high in developing countries, with poor-socioeconomic status (3) , streptococcus pneumonia, Neisseria meningitides, and Haemophilus influenza are mostly detected with documented cases of community-acquired bacterial meningitis (4,5) . In bacterial meningitis, cell number is actually changed, especially the polymorph nuclear cells, as well as hypoglycorrhachia and high CSF protein concentration (6) .…”
Section: Introductionmentioning
confidence: 99%